Metode Waterfall Dalam Rancang Bangun Sistem Informasi Manajemen Kegiatan Masjid Berbasis Web - Hermansyah; Rian Farta Wijaya; Rahmad Budi Utomo (STMIK Budi Darma, 2023)
The mosque is a place used by Muslims for worship and a center for other Muslim activities, such as celebrating holidays, discussions, religious studies, lectures and studying the Qur'an. However, until now many mosques have not been able to take advantage of this extraordinary potential. This is due to the reason that there is still a lack of a system in dealing with administrative matters. Al-Ikhlas Mosque which is located in the village of KotaPari, kecamatan of Pantai Cermin, Kab. Serdang Bedagai is one of the mosques that is lacking in managing mosque activities. The reason is that these activities are less publicized to the congregation of the mosque so that many do not know about the activities at the Al-Ihklas Mosque. Administrative problems are also one of the reasons for the ineffectiveness of the activities carried out by BKM Al-Ikhlas. For this reason, we need a framework that can be used to deal with problems that exist in the Al-Iklhas mosque, Kota Pari. The purpose of building this website is to increase efficiency in managing mosque activities and make it easier for administrators to carry out administrative tasks. This website also helps in monitoring and tracking mosque finances, making it easier for administrators to conduct financial audits. Based on the existing problems, a web-based management information system for the activities of the Al-Iklhas mosque in Kota Pari Village is needed. The mosque activity management web is expected to be able to assist mosque administrators in increasing efficiency and transparency in the management of mosque activities and finances, so as to improve the quality of service to congregations and the community